Portraying the Self-Efficacy of ESA Competition Champions: A Descriptive Case Study - Himmah Al Mardliyah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to explore self-efficacy among the champions of the 2025 ESA Speech Contest. The lack of discussion regarding the self-efficacy of foreign language speech competition participants has prompted this study to examine changes in self-efficacy over time. This study employed a qualitative descriptive case study design with data analyzed using thematic analysis, data were collected through in-depth interviews with the champions. The results showed that in the pre-performance phase, the initial formation of self-efficacy is driven by a strong synergy between social support through consistent teacher evaluation and “peer modeling”, as well as self-regulation utilizing digital media content and “Artificial Intelligence”. Furthermore, in the performance phase, when unexpected stage crises arise such as forgetting the text speech or negative non-verbal responses from the judges, the champions’ self-efficacy revealed its true form as a shield of cognitive resilience. The champions were able to adapt quickly to emerging problems through visual distraction strategies and “cognitive reframing” to maintain their speaking motivation. Finally, in the post-performance phase, this winning experience triggered a generalization effect that restructured self-efficacy sources and reduced fear of negative social judgment, transforming into “everyday speaking courage” in real-life social interactions. This study concluded that the speech competition successfully acted as a psychological intervention that permanently changed participants' communicative behavior and fostered sustainable self-regulation in the future.
:: Finalisasi file repositori 23 Juli 2026_Kurnadi
Keywords: Speaking Self-Efficacy; Speech Competition; Cognitive Resilience; Adaptive Attitude; Self-Regulation